Address to the U. N. Economic and Social Council - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank, reviewed the state of development, and the relationship of economic growth to social equity. First, he summarized recent Bank activities, particularly those which bring the Bank into working relationships with other parts of the U.N. system. Second, he assessed the current state of development in the member countries. Third, he analyzed what he believes to be one of the most critical issues of the entire development process: the relationship of social equity to economic growth. He concluded that the international development community has a grave responsibility to the hundreds of millions of individuals throughout the disadvantaged world for whom these issues are not mere abstractions, but day-to-day realities. He believes, collectively, that touching those lives, and rendering them more livable is possible.